Factors Associated with Pulmonary Tuberculosis in Yogyakarta, Indonesia: A Matched Case-Control Study - Ardyawati Wira Oktaviana; Setyo Sri Rahardjo; Vitri Widyaningsih; Nur Hafidha Hikmayani; Arsita Eka Prasetyawati (Masters Program in Public Health, 2026)
Background: Tuberculosis (TB) remains a public health problem in Indonesia, including in the city of Yogyakarta. The incidence of TB is influenced by various socioeconomic factors, individual characteristics, behavior, and the physical conditions of the home environment. Given these influences, this study aims to analyze the determinants of pulmonary tuberculosis incidence in Yogyakarta, Indonesia. Subjects and Method: This was a matched case-control study. Cases were patients with pulmonary tuberculosis, matched 1:2 by age, sex, and health center area to non-TB controls. Among 168 respondents (56 cases and 112 controls). The study involved 18 community health centers in Yogyakarta, Indonesia, from April to May 2026. Variables included family income, knowledge, attitudes, nutritional status, smoking history, diabetes mellitus, household and close contact history, and housing characteristics. Data were analyzed using bivariate tests and multivariate conditional logistic regression. Results: Family income below the Yogyakarta regional minimum wage (aOR= 0.30; 95% CI= 0.10–0.93), poor tuberculosis knowledge (aOR = 0.27; 95% CI= 0.08–0.95), history of diabetes mellitus (aOR= 0.07; 95% CI= 0.01–0.82), and a confirmed history of close contact with a tuberculosis patient (aOR= 5.12; 95% CI= 1.00–26.09) were independently associated with pulmonary tuberculosis. Respondents who were unaware of their close contact history also had higher odds of tuberculosis (aOR= 3.67; 95% CI= 0.82–16.30), although this association did not reach statistical significance. Conclusion: The incidence of pulmonary tuberculosis in Yogyakarta is significantly associated with family income, tuberculosis-related knowledge, history of diabetes mellitus, and close contact with TB patients. These findings highlight the importance of strengthening active TB case finding through systematic contact investigation not only among household contacts but also in workplaces and industrial settings to facilitate early detection and reduce the risk of tuberculosis transmission